Traumatic posterior fracture-dislocation of the hip joint in adults - Selvey, David M (Department of Health and Rehabilitation Sciences, 2017)
During the period July 1994 to September 1998 surgery was carried out on seventy-six hips in seventy-five patients that sustained posterior fracture-dislocation of their hip joints. During my training I was personally involved in thirteen of these cases and was the primary surgeon in seven cases. Because of my personal interest in these patients Dr Siboto provided me the records of all seventy-five patients for my scrutiny. While he has carried out the surgery on all but the seven cases which I operated on, the literature review, the correlating of the data and all of the interpretation is my own personal work. At surgery prospective records were kept of the degree of comminution of the fracture, the presence of marginal impacting and the presence of fragments in the joint. Fractures were then classified according to Thompson and Epstein (1951). The surgical time was recorded as well as the nature of the associated acetabular floor fracture when it occurred. Anatomical reconstruction was always attempted including elevation of marginal impaction and bone grafting where appropriate. Fragments were only discarded when too small and unattached to permit their inclusion in the reconstruction. All patients had neurological assessment preoperatively and their Sciatic nerves were explored and the state of the nerve recorded at surgery. The process of formulating this dissertation took place over a two-year period from September of 1997 until June of 1999. As a result, the number of patients examined in relationship to a specific subject is not constant but alters according to the group under scrutiny at that particular point in time. An initial review of sixty cases in September 1997 was carried out and then an additional fifteen patients up until September 1998 were included where relevant. The aim of carrying out this study was to gain a better understanding of this injury so that we could formulate a management protocol for our patients in Groote Schuur Hospital. First of all, I reviewed the literature to discover exactly what has been written about this pathology. In the process I hoped to gain a better understanding of the problem and attempt to define a more concise approach to the injury by consolidating the broad array of articles written on this subject. Then by reviewing our findings in our large series of patients I aimed to discover whether we were encountering similar problems to the surgeons who had preceded us and whether we had made any new discoveries that might positively contribute to the future management of these patients.